Inhibitors in Hemophilia A: A Pharmacoeconomic Perspective - Messori, Andrea (Seminars in Thrombosis and Hemostasis, 2018)
A discussion of the main pharmacoeconomic issues related to inhibitors in hemophilia A cannot be separated from an analysis of the most relevant clinical questions. In the field of inhibitors, the clinical evidence includes several controversial topics, such as high-titer versus low-titer inhibitors, the influence of factor VIII products on inhibitor risk, effectiveness of different immune tolerance induction (ITI) treatments, the role of bypassing agents, and development of new non-factor-VIII compounds. In terms of pharmacoeconomic data, numerous cost estimates have been reported in these fields, but this information is strongly influenced by the wide between-country differences in unit costs. Quite reliable data are, however, available regarding expenditure for replacement therapy in patients without inhibitors, increased lifetime costs caused by high-titer inhibitors, and cost of pharmacological interventions aimed at eradicating inhibitors. As regards the cost-effectiveness ratio, the data on ITI are not conclusive; nonetheless, irrespective of the specific treatments employed for inducing tolerance, their costs seem to be offset by the subsequent savings in the cost per patient. Other issues, such as the cost of low-titer inhibitors in patients with hemophilia A and effectiveness of pharmacological interventions aimed at eradicating low-titer inhibitors are not supported by sound data and will require further research. Finally, although the efficacy and safety profiles of novel treatments (e.g., emicizumab, Roche) warrant long-term clinical studies, the economic advantages of these new compounds might be very substantial both in patients with inhibitors and in those at risk of developing inhibitors.
Keywords: hemophilia A; inhibitors; pharmacoeconomics; cost of illness